The girl who speaks bear - Anderson, Sophie (Usborne Publishing Ltd., 2019)
Found abandoned in a bear cave as a baby, and cursed with unusual size and strength, twelve-year-old Yanka the bear has never felt she belonged in the small village where she grew up; the Snow Forest seems to call to her and when she wakes up one day with her legs transformed into bear legs she flees the village, and embarks on a dangerous journey to uncover clues to her mysterious origin and identity.